2008
DOI: 10.1093/ndt/gfn598
|View full text |Cite
|
Sign up to set email alerts
|

Insulin attenuates apoptosis induced by high glucose via the PI3-kinase/Akt pathway in rat peritoneal mesothelial cells

Abstract: Background. Peritoneal mesothelial cells play an important role in peritoneal dialysis and are often exposed to dialysis fluid containing high glucose levels. Loss of peritoneal function is a major complication associated with long-term peritoneal dialysis. In this study, we hypothesized that high glucose levels induce apoptosis, and that insulin attenuates this apoptosis in peritoneal mesothelial cells. To clarify this hypothesis, we examined the effects of insulin on the phosphatidylinositol 3-kinase/Akt sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Furthermore, the development of a novel delivery system to increase local concentrations in the lung epithelial cell milieu without hypoglycemia is a prerequisite for clinical application of insulin to lung diseases, because it was shown that circulating insulin levels with intensive insulin therapy are only transiently higher than in conventional treatment (5), and the antiapoptotic effect of insulin occurred in our in vitro model at concentrations 10-fold higher than physiological levels during a nonfasting state. However, it is not unexpected that more than physiological levels of insulin might be indispensable to demonstrate the antiapoptotic effect, especially in in vitro experimental conditions as used in recent studies (27,41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the development of a novel delivery system to increase local concentrations in the lung epithelial cell milieu without hypoglycemia is a prerequisite for clinical application of insulin to lung diseases, because it was shown that circulating insulin levels with intensive insulin therapy are only transiently higher than in conventional treatment (5), and the antiapoptotic effect of insulin occurred in our in vitro model at concentrations 10-fold higher than physiological levels during a nonfasting state. However, it is not unexpected that more than physiological levels of insulin might be indispensable to demonstrate the antiapoptotic effect, especially in in vitro experimental conditions as used in recent studies (27,41).…”
Section: Discussionmentioning
confidence: 99%
“…Carbon monoxide (CO) (210) can be one of the activators of this pathway in the lung, but insulin can also activate this pathway, which has been demonstrated in other tissues (95,176). PI3K/Akt activates p38 mitogen-activated protein kinase, which activates STAT3, a member of a transcription factor family that decreases Fas expression and caspase-3 activation (210).…”
Section: H1288 Molecular Mechanisms Of Lung Ischemia-reperfusion Injurymentioning
confidence: 99%
“…These pathways phosphorylate serine residues in several subunits of NAD(P)H oxidase (el Benna et al, 1994; Park and Babior, 1997; Dang et al, 1999; Lopes et al, 1999; Babior, 2002, 2004; Simon and Stutzin, 2008). Additionally, it has been reported in rat peritoneal mesothelial cell (RPMC) the participation of the PI3K/Akt pathway in RPMC death induced by high glucose (Kaifu et al, 2009), suggesting that a similar mechanism was implicated in human cells. However, it is unknown if these signaling pathways are involved in HGH solution-induced human peritoneal mesothelial cell (HPMC) death.…”
Section: Introductionmentioning
confidence: 99%